Lifestyle Choices and Brain Health - Mintzer, Jacobo; Donovan, Keaveny Anne; Kindy, Arianne Zokas; Lock, Sarah Lenz; Chura, Lindsay R.; Barracca, Nicholas (Frontiers in Medicine, 2019)
This article is largely based on the activities of the Global Council on Brain Health (GCBH). This article aims to provide an overview of evidence from current literature and expert opinion that reflects the current state of knowledge regarding some of the key elements known to be relevant in preserving brain health. The elements here discussed are not the only ones of importance but rather reflect those that the GCBH has chosen to address since its inception. The areas to be discussed are: mental well-being, exercise, cognitive stimulating activities, sleep, nutrition and social connections. Our review concluded that all these areas offer opportunities to adjust lifestyles and positively impact brain health.